Distribution of Some Airborne Rare Earth Metals, Vanadium and Niobium in the Aswan Arid Area, Egypt - S.M. Hassan, Fatma (Asian Journal of Chemistry, 2010)
Two metals of the lanthanides (lanthanum and cerium) together with four transition metals (scandium, yttrium, vanadium and niobium) have been determined in Aswan dustfall in twelve experimental sites. To reveal the relative metals distribution throughout the town, contour maps and isometric maps have been drawn for each trace metal using an advanced mainframe computer programme. With the exception of vanadium in all sites and cerium in a few sites, the level of trace metals (TM) cotamination of the Aswan topsoils is limited. This will probably be the case until the end of the 21st century, providing there is no major change of anthropogenic sources.